Paclitaxel, Carboplatin, and Bevacizumab in Advanced Cervical Cancer: A Treatment Response and Safety Analysis - Wanjun Tao; Jia Yang; Yongxian Jiang; Wenwen Chen; Yixin Wang (SAGE Publishing, 2020)
Background: Trials reported there are beneficial effects of the addition of bevacizumab to chemotherapy in advanced cervical cancer but might have adverse effects. The purposes of the study were to evaluate the treatment response and safety of the addition of bevacizumab to paclitaxel plus carboplatin in advanced cervical cancer women. Methods: Data on treatment response, adverse effects, and overall survival of women who received paclitaxel plus carboplatin every 3 weeks (ACT cohort, n = 161) or paclitaxel, carboplatin, and bevacizumab every 3 weeks (PCB cohort, n = 127) until disease progression or severe adverse events were collected and analyzed. Results: The treatment response of paclitaxel plus carboplatin increased on addition of bevacizumab ( P = .037). Neutropenia (grade ≥3, P = .001), leukopenia (grade 4, P = .041), anemia (grade ≥3, P = .031), hypertension (grade ≥2, P = .002), and gastrointestinal fistula (grade ≥2, P = 0.006) are reported in the PCB cohort. Women of ACT and PCB cohorts reported an overall survival of 20.11 ± 3.15 months and 24.52 ± 4.05 months, respectively. Conclusions: Addition of bevacizumab increases the treatment response of paclitaxel and carboplatin chemotherapy and overall survival of women with advanced cervical cancers, but it is not well tolerated.